Nerolidol-loaded nanospheres prevent behavioral impairment via ameliorating Na+, K+-ATPase and AChE activities as well as reducing oxidative stress in the brain of Trypanosoma evansi-infected mice - Baldissera M.D. (2017)
© 2016, Springer-Verlag Berlin Heidelberg.The aim of this study was to investigate the effect of nerolidol-loaded nanospheres (N-NS) on the treatment of memory impairment caused by Trypanosoma evansi in mice, as well as oxidative stress, and Na+, K+-ATPase and acetylcholinesterase (AChE) activities in brain tissue. Animals were submitted to behavioral tasks (inhibitory avoidance task and open-field test) 4 days postinfection (PI). Reactive oxygen species (ROS) and thiobarbituric acid-reactive substance (TBARS) levels and catalase (CAT), superoxide dismutase (SOD), Na+, K+-ATPase and AChE activities were measured on the fifth-day PI. T. evansi-infected mice showed memory deficit, increased ROS and TBARS levels and SOD and AChE activities, and decreased CAT and Na+, K+-ATPase activities compared to uninfected mice. N-NS prevented memory impairment and oxidative stress parameters (except SOD activity), while free nerolidol (N-F) restored only CAT activity. Also, N-NS treatment was able to prevent alterations in Na+, K+-ATPase and AChE activities caused by T. evansi infection. A significantly negative correlation was observed between memory and ROS production (p < 0.001; r = −0.941), as well as between memory and AChE activity (p < 0.05; r = −0.774). On the contrary, a significantly positive correlation between memory and Na+, K+-ATPase activity was observed (p < 0.01; r = 0.844). In conclusion, N-NS was able to reverse memory impairment and to prevent increased ROS and TBARS levels due to amelioration of Na+, K+-ATPase and AChE activities and to activation of the antioxidant enzymes, respectively. These results suggest that N-NS treatment may be a useful strategy to treat memory dysfunction and oxidative stress caused by T. evansi infection.